Single versus multi-item self-assessment of sedentary behaviour: A comparison with objectively measured sedentary time in nurses. Issue 9 (September 2018) - Prince, Stephanie A.; Reid, Robert D.; Bernick, Jordan; Clarke, Anna E.; Reed, Jennifer L.
Abstract: Objectives: To compare sedentary time (ST) measured by self-report using a single question from the short-form International Physical Activity Questionnaire (SF-IPAQ), 18-items from the Sedentary Behaviour Questionnaire (SBQ) and objectively using an accelerometer among a large sample of nurses. Design: Cross-sectional. Methods: Participants wore an ActiGraph GT3X accelerometer (≥4 days, ≥10 h/day) and self-reported usual day sitting using the IPAQ and sitting in different modes using the SBQ. Measures were compared using correlations, a Friedman test with Wilcoxon signed-ranks tests for pairwise comparisons, linear regression and Bland–Altman plots. Results: A total of 313 nurses (95% female; mean ± SD: age = 43 ± 12 years) from 14 hospitals participated. Participants self-reported sitting for a median of 240 min/day using the SF-IPAQ and 328 min/day using the SBQ. Median ST measured by the ActiGraph was 434 min/day. All measures were weakly correlated with each other ( ρ = 0.31–40, ps < 0.001). Limits of agreement were wide between all measures. Significant proportional bias between the ActiGraph and the SF-IPAQ and SBQ existed, suggesting that with greater amounts of ST, there is greater disagreement between the self-report and objective measures. Conclusions: In a sample of nurses, self-reported ST using the SF-IPAQ and SBQ was significantly lower than that measured by accelerometer. A single-item tool performed more poorly than a multi-item questionnaire. Future studies should consider including both objective and self-report measures of ST, and where possible use a tool that quantifies ST across multiple domains, define a 'usual day' and are meaningful for those with daily schedule variations such as among shift-worker populations.